LEGALITY OF FINANCIAL RIGHTS OF STATE ADMINISTRATORS SUSPECTED OF CORRUPTION: CAN IT BE QUALIFIED AS AN UNLAWFUL ACT? - Sherly Mevitasari; Jonny Simamora; Herlambang Herlambang (Universitas Bengkulu, 2023)
In carrying out the government system, Law Number 28 of 1999 concerning Good and Clean State Administrators was formed from Corruption, Collusion, and Nepotism which regulates the rights, obligations, prohibitions, and sanctions for state administrators. The consequence of the principle of legality is that in the criminal justice process, the presumption of innocence is imposed until a decision is made. This principle is widely used by state administrators who stumble on corruption to resign when they are named suspects so that they are entitled to pension rights. Therefore, this research aims to describe and analyze the financial rights of state administrators who are suspected of corruption. The method used in this research was descriptive with a normative juridical research design. The legal materials used in this research included primary legal materials, secondary legal materials, and tertiary legal materials. Analyzed using the deductive logic analysis method by interpreting and discussing research result materials based on the definition of law, legal rule, legal theory, and doctrine related to the problem being studied. The results of the data analysis inferred that law enforcement against corruption cases was still not optimal. The law enforcers only looked at criminal offenses committed without looking more broadly at the elements of criminal acts such as locus delicti and tempus delicti so that they could find out the impact and actions of other related criminal acts. Keywords: Legality Principles, State Administrators, State Financial Losses/State Economy, Corruption.